1991
DOI: 10.1007/bf00017927
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of a chalcone isomerase cDNA of Phaseolus vulgaris L.

Abstract: Fig. 1. The nucleotide and derived amino acid sequences of the bean CHI eDNA clone in pCHI1. Potenti~ polyadenyl~ion signals .are underlined.The nucleotide sequence data reported will appear in the EMBL, GenBank and DDBJ Nucleotide Sequence D~abases under the accession number X16470.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…In maize seedlings, previous reports have indicated that IFR is involved in a thiol-independent response to OS under glutathione shortage conditions [57]. Spot B18 protein is identified as chalcone isomerase (CHI, CAA34490, P. vulgaris), a key enzyme in the phenylpropanoid pathway that produces flavonoids and isoflavonoids [58]. Soybean type II CHI with 92% positive homology uses a variety of chalcone substrates, and is specifically activated by nodulation signals.…”
Section: Antioxidant-and Pathogen-related Proteins In O 3 -Stressed Bmentioning
confidence: 99%
“…In maize seedlings, previous reports have indicated that IFR is involved in a thiol-independent response to OS under glutathione shortage conditions [57]. Spot B18 protein is identified as chalcone isomerase (CHI, CAA34490, P. vulgaris), a key enzyme in the phenylpropanoid pathway that produces flavonoids and isoflavonoids [58]. Soybean type II CHI with 92% positive homology uses a variety of chalcone substrates, and is specifically activated by nodulation signals.…”
Section: Antioxidant-and Pathogen-related Proteins In O 3 -Stressed Bmentioning
confidence: 99%
“…The enzyme is a single polypeptide with a molecular mass of 28-29 kDa. CHI genes have been cloned from several plant species (DOONER et al 1991;BLYDEN et al 1991). No CHI genes are known in barley and no investigations on CHI activity have been made.…”
Section: Chalcone Isomerase (Chi)mentioning
confidence: 99%
“…The library was screened sequentially according to Maniatis etal. [26] with the 1.4 kb Eco RI insert from pCHS 1 [39] and with the 808 bp insert ofpCHI1 [3,30] of Phaseolus vulgaris. Five-hundred thousand plaques were screened.…”
Section: Library Construction and Screeningmentioning
confidence: 99%